Vitamin D level in critically ill children 6 months–5 years age admitted to intensive care unit in tertiary care hospital of Central India - Ashok, Akshay; Goel, Manjusha; Chaubey, Bharti; Patil, Rajesh (Indian Journal of Child Health, 2019)
Background: Vitamin D has an important role in maintaining bone health by regulating calcium metabolism in the body. Its level in serum plays a significant role in mortality and morbidity in children Aim: This study aims to determine the Vitamin D levels and its association with clinical outcome in children from the age of 6 months to 5 years admitted to pediatric intensive care unit (PICU). Materials and Methods: A case–control study conducted among children admitted to PICU for a period of 1 year, aged from 6 months to 5 years in the department of pediatrics of a tertiary care institution of Central India. Normal children in the same age group were controls and serum Vitamin D level was assessed by chemiluminescence immunoassay method. Results: The results of this study showed that the prevalence of Vitamin D deficiency was 63% and median Vitamin D and calcium level were 17.70 (13.40–24.97) and 8.90 (7.35–9.26) interquartile range. Among all cases, 6 (9.2%) had severe deficiency, 35 (53.8%) had Vitamin D deficiency, 17 (26.2%) had insufficiency, and only 7 (10.8%) had normal level. Conclusion: This study concludes that the proportion of Vitamin D deficiency was higher in critically ill children, as compared to healthy children, but no statistically significant association was found between the deficiency and outcome among critically ill children.